Bryophytes for the linear barrier as a PM2.5 mitigation technology in the urban landscape - Kārkliņa, Juta; Kārkliņš, Edgars; Ābele, Lilita; Strazdiņa, Līga (Landscape Architecture and Art, 2024)
Air pollution has been recognized by the World Health Organization as a global problem, resulting in 9-12 million deaths annually, and particulate matter is the most severe threat to human health. Particulate matter can be distinguished by its size, as PM2.5 has a diameter of 2.5 μm or less, meaning that these tiny dust particles are invisible to the naked eye. Various solutions are being sought for the problem of air pollution, which resonate with landscape architecture solutions, such as Green Infrastructure and linear (vertical) barriers. They are being researched as an effective nature-based solution to the growing air pollution problem that organically blends into the urban landscape. Evaluations of various plants for their pollution abatement potential highlight bryophytes as particularly effective due to their high absorption capacity, and to ensure the sustainability of the linear barrier, cultivation under controlled conditions is recommended. This paper investigates the cultivation of bryophytes under controlled conditions and identifies the most effective moss species during a practical experiment. This experiment and paper are part of a larger, more extensive study on air pollution reduction using bryophytes, and the research described in this paper is instrumental in future research. The assessed bryophyte species will be further investigated for their ability to absorb air pollution PM2.5. This paper uses research methods such as literature analysis and a laboratory experiment conducted between January and April 2024.